Heard on the Iowa Birdline, September 15-November 15, 1995 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1995)
Summary of the Iowa Birdline update for September 15-November 15, 1995. Highlights of the update include sightings of a juvenile Sharp-tailed Sandpiper and a Clark's Grebe. Other interesting observations were of a drake Eurasian Wigeon, a Red Phalarope, and a report of two Hummingbirds that were visiting feeders in November. Also of note were the variety of rare gulls that were seen throughout the state. Epson - sheet feed